Kampung Adat Dalam Potret Akuntabilitas: Suatu Kajian Etnografi - Sesmi Oktavia; Hidayatul Ihsan; Rasyidah Mustika (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This research aims to understand the accountability of indigenous village management. Specifically, the focus of this research is to explain how indigenous village managers demonstrate accountability in terms of five dimensions, namely, transparency, liability, control, responsibility, and responsiveness. In addition to the dimensions of accountability, stakeholder theory is also used in understanding the accountability of managers to stakeholders. Furthermore, this research was conducted using an ethnographic design, in which the Sijunjung Traditional Village was chosen as the object of research. The research findings indicate that indigenous village managers have demonstrated accountability through the accountability dimensions of transparency, liability, control, responsibility and responsiveness, but improvements in some aspects are still needed. Therefore, indigenous village managers need to establish work programs and a clear vision and mission, improve responses to stakeholder input and complaints, and implement an efficient and technology-based complaints system.